Yehyatonhserayenteri: A Haudenosaunee Model for Onkwehon:we (Indigenous) Education - Whitlow, Kawennakon Bonnie; Oliver, Vanessa; Anderson, Kim; Brozowski, Kari; Tschirhart, Stephanie; Ransom, Kaienkwinehtha (Canadian Journal of Education/Revue canadienne de l’éducation, 2019)
Focusing on Onkwehon:we (Indigenous) ways of knowing, and Haudenosaunee ways of knowing in particular, this article showcases the strengths of Onkwehon:we-led education and leadership. Under the leadership of our Youth Advisory Council, 22 young people (11 Onkwehon:we and 11 non-Onkwehon:we) took part in three days of workshops on Six Nations. The workshops were led and conducted by Haudenosaunee knowledge keepers who covered a range of topics. Six months after the completion of the workshops, 18 of the 22 youth participated in one-on-one follow-up interviews. We also conducted community impact interviews with 10 adult community members from Six Nations and Brantford. Through the workshops and interviews, we learned that Nation-specific learning helped to inform non-Onkwehon:we youth about the history of the lands on which they live, granting them access to traditions and ceremonies that resonated with them in both emotional and intellectual ways. Through experiential education and Haudenosaunee leadership, both Onkwehon:we and non-Onkwehon:we youth learned to value the original instructions, build relationships, and address the challenges of decolonization in an increasingly uncertain world.